2020
DOI: 10.1101/2020.02.21.940650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AutoGeneS: Automatic gene selection using multi-objective optimization for RNA-seq deconvolution

Abstract: Tissues are complex systems of interacting cell types. Knowing cell-type proportions in a tissue is very important to identify which cells or cell types are targeted by a disease or perturbation. When measuring such responses using RNA-seq, bulk RNA-seq masks cellular heterogeneity. Hence, several computational methods have been proposed to infer cell-type proportions from bulk RNA samples. Their performance with noisy reference profiles highly depends on the set of genes undergoing deconvolution. These genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…The data that support the findings of this study are openly available Jian Jiang 1,2 Alen Faiz 1,3,4 Marijn Berg 1,2 Orestes A. Carpaij 1,3 Corneel J. Vermeulen 1,3 Sharon Brouwer 1,2 Laura Hesse 1,2 Sarah A. Teichmann 5,6,7 Nick H. T. ten Hacken 1,3 Wim Timens 1,2 Maarten van den Berge 1,3 Martijin C. Nawijn 3,5…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tsupporting
confidence: 54%
“…The data that support the findings of this study are openly available Jian Jiang 1,2 Alen Faiz 1,3,4 Marijn Berg 1,2 Orestes A. Carpaij 1,3 Corneel J. Vermeulen 1,3 Sharon Brouwer 1,2 Laura Hesse 1,2 Sarah A. Teichmann 5,6,7 Nick H. T. ten Hacken 1,3 Wim Timens 1,2 Maarten van den Berge 1,3 Martijin C. Nawijn 3,5…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tsupporting
confidence: 54%
“…Deconvolution of bulk RNA-seq alveolar macrophage signatures was performed using AutoGeneS v1.0.3 68 and signatures derived from the integrated single-cell RNA-seq object. We used an integrated single-cell RNA-seq object containing the first six subjects included into analysis (patients 1-6) to train the AutoGeneS model.…”
Section: Deconvolution Of Bulk Rna-seq Alveolar Macrophage Signaturesmentioning
confidence: 99%
“…To gather additional empirical support from COVID-19 patients, we downloaded the bulk RNA-seq data of PBMCs from three severe COVID-19 patients and three healthy controls 31 and applied AutoGeneS 32 to deconvolute the composition of the cell clusters based on the signature genes identified in our single-cell analysis. Our results indicated that there were significantly more severe stage-specific monocytes (cluster 9), plasma B cells (cluster 11), and proliferating CD8 + T cells (cluster 12) in severe COVID-19 patients than in healthy controls ( Supplementary Fig.…”
Section: Enhancement Of Humoral and Cellular Immune Responsesmentioning
confidence: 99%
“…Deconvolution of cell clusters from bulk RNA-seq data. We applied Auto-GeneS 32 to deconvolute the composition of the cell clusters based on the signature genes identified in our single-cell analysis. Specifically, we first obtained a gene-bycluster expression matrix from our normalized single-cell profile, in which the matrix elements represented the average expression of each gene in each cell cluster.…”
Section: R S C R S C R S C R S C R S C R S C R S C R S C R S C R S mentioning
confidence: 99%